GeoGebra Classic: Learning of Euclidean geometry in students with multiple subject teaching (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of this study is to identify the effectiveness of the application of GeoGebra Classic as a mediationsoftware for learning Euclidean geometry in students with multiple subject teaching. The method employed was quasiexperimentalresearch using a non-equivalent control group design. The subjects of this study were students of theInstituciónEducativa Particular Ciudad de Lima. The data were required through McNemar and Pearson Correlation tests. Theresults show an increase in the improvement of self-regulation cognitive skills from 25 % to 61 %, for an increase of 36 % afterapplying GeoGebra Classic. An improvement in learning was evidenced since the correlation coefficient is high (0.725) forlearning with software compared to (0.442) for the traditional method. This indicates that there is an impact of the use of theGeoGebra Classic application on the learning outcomes in students, adopting the hypothesis: Teaching Euclidean geometrymediated with GeoGebra Classic improves self-regulation skills in students. It can be concluded that this could be due to theinterest of the students, denoting that the low academic performance of the control group was above the level of the goodperformers.